Anti-inflammatory and anti-biofilm properties of ent-nemorosone from Brazilian geopropolis. (October 2016) - da Cunha, Marcos Guilherme; Franchin, Marcelo; de Paula-Eduardo, Laila Facin; Freires, Irlan Almeida; Beutler, John A.; de Alencar, Severino Matias; Ikegaki, Masaharu; Tabchoury, Cinthia Pereira Machado; Cunha, Thiago Mattar; Rosalen, Pedro Luiz
Highlights: ent -Nemorosone had no reports about its anti-inflammatory and anti-biofilm activities. ent -Nemorosone reduced the TNF-α production by acting on ERK1/2 and NF-kB. ent -Nemorosone reduced the biofilm adherence by acting on polysaccharide formation. Abstract: ent -Nemorosone is a benzophenone isolated from geopropolis from Melipona scutellaris whose biological properties remain unexplored. Herein, we evaluated the anti-inflammatory activity of ent -nemorosone by in vivo neutrophil migration and TNF-α quantification, as well as by in vitro TNF-α quantification, ERK 1/2 phosphorylation, NF-kB activation and nuclear translocation of p65 in stimulated macrophages. ent -Nemorosone was also tested for its antimicrobial effects against Streptococcus mutans biofilm adhesion, polysaccharide production, and viability. ent -Nemorosone reduced the influx of neutrophils and TNF-α release into the peritoneal cavity of mice, as well as the in vitro TNF-α levels, ERK 1/2 phosphorylation, NF-kB activation and nuclear p65 translocation. Furthermore, this compound inhibited biofilm adhesion and reduced the amount of extra- and intracellular polysaccharides synthesized by S. mutans . Thus, ent -nemorosone showed promising anti-inflammatory activity by acting on TNF-α release in macrophages, as well as anti-biofilm properties by reducing S. mutans polysaccharide production.